Attitude towards academic survey among audit firms in Malaysia: some challenges - Puat Nelson, Sherliza; Ahmad, Maslina; Zainal Abidin, Nor Hafizah (Penerbit UMT, 2019)
In the past, it was common among the accounting domain literature to document studies on the avenue of behavioural aspects. Many past behavioral literature captures the ethical attitudes, or ethical intentions towards certain area of decision making and perceptions. Likewise, very seldom do we encounter research on the avenue of behavioural of accountants towards survey. In the current study, we investigate the behaviour of accounting practitioners towards survey. We sent surveys to these accounting practitioners at the end of the year starting from October 2017, just before the peak season starts. The mailing list of audit firms in Malaysia was obtained from the Malaysian Institute of Accountants (MIA) for a nationally representative, convenience sample. A total of 119 firms were finally sent a set of questionnaire surveys regarding independence and ethical requirements. Recipients were asked to complete the questionnaires, and the completed questionnaires would be collected by hand later. The purpose of our research is to document the behaviour of practitioners towards academic survey. This came to light due to our recent encounter with audit firms when collecting data on questionnaire surveys. The responses were very discouraging. Hence motivated us to examine and document the responses of these practitioners towards academic survey.